Drivers of nutritional change in four South Asian countries: A dynamic observational analysis - Headey, Derek D.; Hoddinott, John F.; Park, Seollee (Wiley, 2016)
This paper quantifies the factors explaining long‐term improvements in child height for age z‐scores in Bangladesh (1996/1997–2011), India (1992/1993–2005/2006), Nepal (1997–2011) and Pakistan (1991–2013). We apply the same statistical techniques to data from a common data source from which we have extracted a set of common explanatory variables that capture ‘nutrition‐sensitive’ factors. Three are particularly important in explaining height for age z‐score changes over these timeframes: improvements in material well‐being; increases in female education; and improvements in sanitation. These factors have comparable associations across all four countries.